The Application of Goat Manure and Rhizobium on Contaminated Soil to Improve Growth and Yield of Mung Bean (Vigna radiata, L) - Akhlan Muhammad Akbar; Farhan Hidayat; Muhamad Sufyan Rafid; Ida Setya Wahyu Atmaja (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2026)
Stone slurry, a byproduct of natural stone industry activities, has the potential to pollute agricultural land surrounding the industry, affecting both the physical and chemical properties of the topsoil. The aim of this research was to analyze the effect of goat manure and Rhizobium application on stone slurry-contaminated soil in order to improve the growth and yield of mung bean (Vigna radiata L.). A randomized block design (RBD) was arranged, including two factors: the doses of goat manure with three levels, namely 0 ton ha-1, 10 ton ha-1, 15 ton ha-1, and the doses of Rhizobium with three levels, 0 g kg-1 of seed, 7.5 g kg-1 of seed, and 15 g kg-1 of seed. The results showed that goat manure application had an independent effect on plant height and number of leaves at 28 days after planting (DAP), as well as on the number of pods per plot. Goat manure increased plant height and pod number by approximately 12-14% compared with the control treatment. However, its effect decreased during subsequent observation periods. Meanwhile, Rhizobium application did not significantly affect on all observed variables. Soil pH, nutrient availability, and soil physical properties as limiting factors affecting microbial activity, including both organic matter-decomposing microorganisms and Rhizobium as a nitrogen-fixing bacterium.